The determinant of equity financing in sharia banking and sharia business units - Jaenal Effendi (Economic Journal of Emerging Markets, 2018)
Equity financing plays an important role in mobilizing financing in the real sector. The core business of sharia banking is based on the real sector, but the financing portion in sharia banking is still dominated by debt financing. This study aims to analyze the factors that affect equity financing in General Sharia Bank (BUS) and Sharia Business Unit (SBU) in Indonesia. This study uses Error Correction Model. The results show that in the long-term model of Third Party Fund (DPK), Finance to Deposit Ratio (FDR), Non-Performing Financing (NPF), Inflation and Interest Rates Credit of Conventional Bank (SBK) has a significant positive effect on equity financing. BOPO variables (Operating Cost Ratio to the Operating Income) and Return on Assets (ROA) have a positive but not significant effect on equity financing. The DPK and FDR variables have a positive and significant effect on equity financing on the short-term model.